Studies in Italian Sacred and Instrumental Music in the 17th Century - Bonta, Stephen (Aldershot Ashgate, 2003)
Stephen Bonta's research on seventeenth-century Italian music, particularly for strings, spans more than 30 years. Included in this selection of his published articles is his seminal study of the early history of the bass violin which proved to be the foundation for his subsequent articles on the early history of the violoncello. In addition to the discussions of secular instrumental music, the volume features essays that explore Italian sacred music of the period, including Monteverdi's Marian Vespers.
Keywords: 17th Century (1601-1700); Music history; Church music; Instrumental music; Italy